Biomedical analysis of fibrinolytic enzyme produced by microorganism from poultry farm; an in vitro study (International Journal of Food and Nutritional Sciences, 2022)
Fibrinolytic enzymes have immense importance in the field of biomedicine due to their potential therapeutic applications. In recent years, microbial fibrinolytic enzymes have been reported to treat cardiovascular diseases. The aim of the present study is to analyze the biomedical application of fibrinolytic enzyme produced by microorganism isolated from poultry farm. The isolated bacterial strains from soil samples enriched with poultry waste were screened for their fibrinolytic activity. The fibrinolytic enzyme was produced from the screened isolate by enriching the medium with nutrient sources such as carbon sources, nitrogen sources, natural sources etc. Our finding clearly depicts the clot lytic activity and thrombolytic activity of the fibrinolytic enzyme in a dose dependent manner. The fibrinolytic enzyme exhibited cardioprotective and wound healing activities.